2020
DOI: 10.1038/s41598-020-65785-5
|View full text |Cite
|
Sign up to set email alerts
|

In vitro genomic damage induced by urban fine particulate matter on human lymphocytes

Abstract: Urban air pollution represents a global problem, since everyday many mutagenic and carcinogens compounds are emitted into the atmosphere, with consequent adverse health effects on humans and biota. Specifically, particulate matter air pollution was associated with increased risks in human mortality and morbidity. In this paper, we analyse the genomic effects on human lymphocytes of different concentrations of annual Turin PM2.5 extract by an in vitro micronuclei assay. Samplings were collected from an urban me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 40 publications
0
3
0
Order By: Relevance
“…Particle-size fractions PM 10 (suspended PM with an aerodynamic diameter < 10 μm) and especially the smaller ones (PM 2.5 and PM 1 , with aerodynamic diameters less than 2.5 and 1 μm, respectively) pose a significant health problem because they can penetrate the lungs and even the bloodstream [ 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 ]. For an estimation of population-weighted exposure to ambient particulate air pollution, the average levels of PM 2.5 particle fraction concentrations are most commonly used, as this fraction is capable of penetrating deep into the lungs and causing severe, negative health effects [ 27 , 28 , 29 ]. However, the choice of fraction often depends on the availability of air pollution data.…”
Section: Introductionmentioning
confidence: 99%
“…Particle-size fractions PM 10 (suspended PM with an aerodynamic diameter < 10 μm) and especially the smaller ones (PM 2.5 and PM 1 , with aerodynamic diameters less than 2.5 and 1 μm, respectively) pose a significant health problem because they can penetrate the lungs and even the bloodstream [ 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 ]. For an estimation of population-weighted exposure to ambient particulate air pollution, the average levels of PM 2.5 particle fraction concentrations are most commonly used, as this fraction is capable of penetrating deep into the lungs and causing severe, negative health effects [ 27 , 28 , 29 ]. However, the choice of fraction often depends on the availability of air pollution data.…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have shown that urban fine particulate matter (PM) has mutagenic and genotoxic activities in different short-term tests on bacteria and in vitro and in vivo human cells [ 1 , 2 , 3 , 4 , 5 , 6 ]. The genotoxic and mutagenic activity of PM varies according to its size and physical and chemical composition that depends mainly on local emissions [ 3 , 7 , 8 , 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…We focused on moderate extreme events regarding mortality by defining the 31-day-moving 95th percentile as the threshold for cancer-related mortality events. The medical evidence states that carcinogenesis is mostly affected by long-term factors, i.e., persistent exposure to pollutants, such as particulate matter [14,[37][38][39]. Short-term effects place an additional burden on cancer patients.…”
Section: Discussionmentioning
confidence: 99%